2003
DOI: 10.1097/01.ju.0000050648.40164.0d
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin and Maspin are Inversely Expressed in Laser Capture Microdissectioned Prostate Cancer

Abstract: We conclude that the increased ratio of hepsin-to-maspin may have an important role in prostate cancer progression and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 15 publications
6
35
0
2
Order By: Relevance
“…The marked elevation of hepsin in malignant prostate tissues and correlation with increasing Gleason score were in agreement with other data from microarray analyses and real-time PCR studies (Dhanasekaran et al, 2001;Stamey et al, 2001;Ernst et al, 2002;Chen et al, 2003;Riddick et al, 2003;Stephan et al, 2004). The functional importance of hepsin has been shown by its overexpression in a transgenic mouse model of prostate tumorigenesis, which led to basement membrane disorganisation and enhanced metastasis (Klezovitch et al, 2004).…”
Section: Serine Proteases and Inhibitorssupporting
confidence: 75%
See 2 more Smart Citations
“…The marked elevation of hepsin in malignant prostate tissues and correlation with increasing Gleason score were in agreement with other data from microarray analyses and real-time PCR studies (Dhanasekaran et al, 2001;Stamey et al, 2001;Ernst et al, 2002;Chen et al, 2003;Riddick et al, 2003;Stephan et al, 2004). The functional importance of hepsin has been shown by its overexpression in a transgenic mouse model of prostate tumorigenesis, which led to basement membrane disorganisation and enhanced metastasis (Klezovitch et al, 2004).…”
Section: Serine Proteases and Inhibitorssupporting
confidence: 75%
“…Similarly, little is known of the potential roles of the transmembrane serine proteases and their inhibitors. However, recent data from microarray profiling studies have linked hepsin with prostate cancer pathogenesis (Dhanasekaran et al, 2001;Stamey et al, 2001;Ernst et al, 2002;Chen et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepsin RNA levels were found to be low in normal prostate and benign hyperplasia but strongly increased in prostate carcinoma, particularly in advanced stages (8 -10). Hepsin protein staining with a monoclonal anti-hepsin antibody showed that hepsin expression was highest at sites of bone metastasis and in late stage primary tumors (12), which is consistent with the finding that increased hepsin RNA levels correlated with higher Gleason grades and tumor progression (7)(8)(9)(10)13). In contrast, using a different antibody Dhanasekaran et al (6) found the strongest hepsin expression in high grade prostate intraneoplastic lesions and lower expression in primary carcinoma and in metastatic lesions.…”
supporting
confidence: 75%
“…A number of molecular profiling studies of human prostate carcinoma have been previously published using grossly dissected tissue specimens. 4 -8 More recent work 9,10 has shown the feasibility of gene expression profiling studies using pure populations of cells obtained with laser capture microdissection (LCM). 11 We modified established protocols [12][13][14] for analyzing mRNA from microdissected frozen tissues and applied this protocol to ethanol-paraffin tissue.…”
Section: (J Mol Diagn 2004 6:371-377)mentioning
confidence: 99%